2015
DOI: 10.1186/s12885-015-1673-3
|View full text |Cite
|
Sign up to set email alerts
|

Tumour biology, metastatic sites and taxanes sensitivity as determinants of eribulin mesylate efficacy in breast cancer: results from the ERIBEX retrospective, international, multicenter study

Abstract: BackgroundOur retrospective, international study aimed at evaluating the activity and safety of eribulin mesylate (EM) in pretreated metastatic breast cancer (MBC) in a routine clinical setting.MethodsPatients treated with EM for a locally advanced or MBC between March 2011 and January 2014 were included in the study. Clinical and biological assessment of toxicity was performed at each visit. Tumour response was assessed every 3 cycles of treatment. A database was created to collect clinical, pathological and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
36
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 19 publications
8
36
2
Order By: Relevance
“…On the other hand, the ERIBEX trial, a retrospective, international, multicenter study involving 258 patients receiving eribulin for a locally advanced or metastatic breast cancer, HER2 positivity seemed to be a predictive factor, with a significant increase in clinical benefit rate in HER2 positive tumors compared to those HER2 negative (HR 0.38, p = 0.02). This could be probably due to the systematic use of trastuzumab in association with eribulin, in the population of ERIBEX study [24]. In our Cox proportional hazards model, there was no significant difference in PFS according to hormone receptor expression and HER2 positivity, even if HR values for hormone-positive disease were near or superior to 1, thus suggesting potentially worse PFS curves in these patients.…”
Section: Discussionmentioning
confidence: 72%
“…On the other hand, the ERIBEX trial, a retrospective, international, multicenter study involving 258 patients receiving eribulin for a locally advanced or metastatic breast cancer, HER2 positivity seemed to be a predictive factor, with a significant increase in clinical benefit rate in HER2 positive tumors compared to those HER2 negative (HR 0.38, p = 0.02). This could be probably due to the systematic use of trastuzumab in association with eribulin, in the population of ERIBEX study [24]. In our Cox proportional hazards model, there was no significant difference in PFS according to hormone receptor expression and HER2 positivity, even if HR values for hormone-positive disease were near or superior to 1, thus suggesting potentially worse PFS curves in these patients.…”
Section: Discussionmentioning
confidence: 72%
“…[19][20][21] Gamucci et al 19 reported a favourable efficacy/safety ratio for eribulin in a multicentre observational Italian study involving 133 patients with MBC previously treated with at least two chemotherapy lines. Compared with our experience, the rates of overall response and stable disease were nearly identical (partial response 21.1% vs 17.5%, stable disease 42.8% vs 46.7%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several studies have demonstrated that eribulin is clinically-effective in patients with breast cancer (14,15). In a pooled analysis of patients with metastatic breast cancer who had received at least one prior chemotherapy regimen, eribulin significantly extended overall survival (OS), and increased the progression-free survival (PFS) and clinical benefit rates compared with the control treatments (15).…”
mentioning
confidence: 99%